Text on front: 'Treasurer Sindicato de Trabajadores de Embotelladora Guatemalteca (Coca-Cola). Dec. 12, 1978-Dec. 12, 1979. He died for his fellow workers'
Text on front: 'Treasurer Sindicato de Trabajadores de Embotelladora Guatemalteca (Coca-Cola). Dec. 12, 1978-Dec. 12, 1979. He died for his fellow workers'.